The Relationship Between Mental Health, Self-Confidence, and Self-Control with Fatherless in Grade IX Students - Berlian Hakim Arief; Rusnoto Rusnoto; Anny Rosiana Masithoh (Advances in Healthcare Research, 2026)
Purpose: This study aimed to analyze the relationship between mental health, self-confidence, and self-control with fatherlessness among grade IX students at SMP Negeri 4 Bae Kudus. The hypothesis proposed that poorer mental health, lower self-confidence, and weaker self-control are significantly associated with higher fatherlessness. Research Method: This research used an analytical observational design with a cross-sectional approach. The population consisted of 212 grade IX students, and 139 respondents were selected using Slovin’s formula with proportional random sampling. Data were collected using structured questionnaires, including the MHC-SF, self-confidence scale, self-control scale, and Father Presence Questionnaire, then analyzed using univariate and Chi-Square tests. Results and Discussion: The findings showed significant relationships between mental health and fatherlessness (p=0.000), self-confidence and fatherlessness (p=0.000), and self-control and fatherlessness (p=0.003). These results indicate that lower paternal involvement is associated with poorer psychological well-being, reduced confidence, and weaker self-regulation among adolescents. Implications: The findings highlight the importance of fathers’ emotional presence in adolescent development and suggest strengthening family-based interventions and school counseling support, as well as further research on paternal involvement and adolescent well-being